Biosynthesis amylase and proteinase of some halophilic bacterial strain from shrimp culture ponds - Tuyet Minh, Phan Thi; Chinh, Tang Thi (Academia Journal of Biology, 2014)
By the screening sediements of shrimp culture pond, we selected two bacterial strains NB4 and CHP6, these bacterial strains could biosynthesize enzymes amylase and proteinase. They could grow and produced amylase and proteinase in the media with NaCl concentration ranged from 0% to 10%. The optimum sodium concentration of the media for their production of amylase was 5% NaCl and for their production of proteinase was 2% NaCL. These bacterial strains were halophilic microorganisms. These bacterial could grow and biosynthesize amylase and proteinase in the media with a range of incubation temperature from 20oC to 40oC, but most suitable temperature for their production of these enzymes were 30oC - 35oC. The optimum pH for biosyntheses amylase and proteinase were 6.5 - 8.5. The highest biosynthesis of amylase occurred in media used starch as carbon source and beef extract as nitrogen source. The highest biosynthesis of proteinase in media contained glucose and soybean powder. The media containing organic nitrogen sources were suitable for the biosyntheses of mentioned above enzymes. The media containing inorganic nitrogen likes nitrogen source were very fragile for their production of amylase and proteinase. These strains could not grown and produced amylase and proteinase in the media containing ammonium sulfate as nitrogen source.